2013
DOI: 10.5006/0553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FeCO3 Supersaturation and Carbide Exposure on the CO2 Corrosion Rate of Carbon Steel

Abstract: The pH stabilization technique is a widely used corrosion protection method for multiphase gas pipelines with glycol as hydrate inhibitor. It implies to increase the pH by addition of  3 HCO in order to enhance the formation of protective iron carbonate films. The protection mechanism at ~20°C is of concern because the conditions for precipitating protective corrosion film are less favorable compared to higher temperatures due to the increasing solubility of FeCO 3 with decreasing temperature. The scope of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 22 publications
6
51
0
1
Order By: Relevance
“…Similar corrosion product morphologies have been observed recently under different experimental conditions. [19][20] Furthermore, it is known that the nucleation and growth of the inner FeCO 3 typically starts at the steel surface because of the highest pH and FeCO 3 saturation values achieved there. 21 This is because of the Fe 3 C layer restricting the transport of acidic species in and ferrous ions out, so the most favorable conditions for the precipitation of a protective FeCO 3 layer are found inside the porous Fe 3 C layer at the steel interface.…”
Section: Corrosion-january 2014mentioning
confidence: 99%
“…Similar corrosion product morphologies have been observed recently under different experimental conditions. [19][20] Furthermore, it is known that the nucleation and growth of the inner FeCO 3 typically starts at the steel surface because of the highest pH and FeCO 3 saturation values achieved there. 21 This is because of the Fe 3 C layer restricting the transport of acidic species in and ferrous ions out, so the most favorable conditions for the precipitation of a protective FeCO 3 layer are found inside the porous Fe 3 C layer at the steel interface.…”
Section: Corrosion-january 2014mentioning
confidence: 99%
“…9 In Part 1 of this study, 7 the presence of iron carbide (Fe 3 C) on the steel surface was detected using XRD analysis. Farelas, et al, 10 and Berntsen, et al, 11 reported as well the presence of a Fe 3 C layer resulting from the preferential dissolution of ferrite over Fe 3 C. Fe 3 C is an electrical conductor 12 and its presence will increase the apparent crosssectional area of the ER element and decrease the element's electrical resistance (Equation [1]), which results in lowering the corrosion rate reading, as is observed in Figure 2.…”
Section: Experimental Study Of Corrosion In Co 2 /Oil/ Water Environmmentioning
confidence: 71%
“…This affects the kinetics of dissolution and in turn the mechanisms the corrosion products precipitate with, and their properties. Depending on the local pH, and on the local Fe+normalH2CO32FeCO3+2normalH++2normale and intermediate adsorbents concentrations, (resulting from the dissolution process), and on the applied potentials, the initially carbonate‐based corrosion products precipitate by supersaturation, (Equation (5)), or by direct oxidation, (Equation (6)). Fe2++CnormalO32FeCO3 Fe+normalH2CO32FeCO3+2normalH++2normale …”
Section: Resultsmentioning
confidence: 99%